A call for language assessment literacy in the education and development of teachers of English as a foreign language - Herrera, Leonardo; Macías, Diego Fernando (Colombian Applied Linguistics Journal, 2015)
Even though assessment constitutes an essential component of any educational process, many teachers seem to ignore its multiple implications and manifestations. Assessment continues to be regarded mainly as the summative evaluation which informs teachers of students’ success or failure in their learning process based on a numeric scale. This narrowed approach may be due in part to the lack of preparation and training both in teacher education and professional development programs. This paper thus aims to raise awareness of the relevance of Language Assessment Literacy (henceforth LAL) in the field of teaching English as a Foreign Language (EFL) by examining some definitions of assessment, reviewing various studies in the area, analysing some models and alternatives for the evaluation and development of LAL in EFL teaching, and finally, offering conclusions and recommendations for the development of LAL among EFL teachers to better serve the needs of their students and their institutions.